Strategi EOQ untuk Efisiensi Pengelolaan Persediaan Obat di Rumah Sakit Primer dalam Mendukung Kelancaran Pelayanan Kesehatan - Asri, Fusarina Mumpuni Intantyana; Kurniawan, Aris; Chalidyanto, Djazuly; Prayitno, Antonius Adji (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study evaluated drug inventory management in a primary hospital pharmacy using the Economic Order Quantity (EOQ) method. A descriptive quantitative design was applied with secondary data collected from January to December 2024, covering annual demand, purchase price, ordering cost, and holding cost. The analysis revealed inefficiencies, as several drugs simultaneously faced overstock and stock out risks, indicating weaknesses in procurement planning. EOQ calculations suggested lower and more frequent procurement, reducing storage costs and improving stock control. The findings demonstrated that applying EOQ could minimize financial risks, optimize resource allocation, and ensure continuous access to essential medicines. This research highlights the relevance of structured inventory models in supporting hospital efficiency and sustainable pharmaceutical logistics, particularly in resource-limited primary hospitals.